The Evolution of AIFA Registries to Support Managed Entry Agreements for Orphan Medicinal Products in Italy - Entela Xoxi; Karen M Facey; Americo Cicchetti (Frontiers Media S.A., 2021)
Italy has a well-established prominent system of national registries to support managed entry agreements (MEAs), monitoring innovative medicinal products (MPs) with clinical as well as economic uncertainties to ensure appropriate use and best value for money. The technological architecture of the registries is funded by pharmaceutical companies, but fully governed by the national medicines agency (AIFA). A desktop analysis was undertaken of data over a 15-year timeframe of all AIFA indication-based registries and associated EMA information. The characteristics of registries were evaluated, comparing orphan MPs vs. all MPs exploring cancer and non-cancer indications. OMP (orphan medicinal product) registries' type vs. AIFA innovation status and EMA approval was reviewed. Of the 283 registries, 182 are appropriateness registries (35.2% relate to OMPs, with an almost equal split of cancer vs. non-cancer for OMPs and MPs), 35 include financial-based agreements [20% OMPs (2 non-cancer, 5 cancer)], and 60 registries are payment by result agreements [23.3% OMPs (4 non-cancer, 10 cancer)]. Most OMPs (53/88) came through the normal regulatory route. With the strengthening of the system for evaluation of innovation, fewer outcomes-based registries have been instigated. AIFA has overcome many of the challenges experienced with MEA through developing an integrated national web-based data collection system: the challenge that remains for AIFA is to move from using the system for individual patient decisions about treatment to reviewing the wealth of data it now holds to optimize healthcare.